2018
DOI: 10.3390/agronomy8090184
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Fructan Exohydrolase Activity and the Quality of Helianthus tuberosus L. Tubers

Abstract: Jerusalem artichoke tubers have diverse applications in the food industry as well as in biotechnology. Their suitability depends mostly on the inulin content. Seasonal fluctuations of fructan exohydrolase activity responsible for inulin degradation was investigated in the tubers of three Jerusalem artichoke cultivars. The changes of fructan exohydrolase activity positively correlated with the changes of the content of total and short fructooligosaccharides. Therefore, to extract inulin with higher degree of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The results of this study are compatible with these conditions. Moreover, the findings demonstrated that seasonality significantly impacted Jerusalem artichoke growth, consistent with earlier studies (Zorić et al, 2016;Krivorotova and Sereikaite, 2018).…”
Section: Argumentation Of the Response Results Of Environmental Varia...supporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are compatible with these conditions. Moreover, the findings demonstrated that seasonality significantly impacted Jerusalem artichoke growth, consistent with earlier studies (Zorić et al, 2016;Krivorotova and Sereikaite, 2018).…”
Section: Argumentation Of the Response Results Of Environmental Varia...supporting
confidence: 91%
“…After 2007, the grains and green grain crops as raw materials for biomass energy were banned in China (Xue et al, 2016;Qaseem and Wu, 2021), so the non-food biomass feedstock is the first choice of bioenergy production in China (Qaseem and Wu, 2021). FAO experts have dubbed Jerusalem artichoke (Helianthus tuberosus L.) a "21st-century human livestock crop" because of its high tolerance to environmental challenges such as soil salinity, drought, and plant diseases (Long et al, 2016;Krivorotova and Sereikaite, 2018), making it ideal for marginal lands. Moreover, with rapid growth and low production cost (such as fewer pesticides input, fertilizers, and water) (Bogucka et al, 2021), as well as high biomass (Bogucka and Jankowski, 2020), Jerusalem artichoke is regarded as one of the most promising bioenergy raw material sources (Epie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tuber juice can be used in the treatment of hemorrhoids, conjunctivitis, blepharitis and dermatitis as well as psoriasis, ulcers and burns (84,85). The juice also improves blood flow to all parts of the gastrointestinal and pancreatic mucosa, and thus plays an important role in the treatment of chronic disorders, such as: stomach, intestinal, colon, pancreas inflammation, etc.…”
Section: Pharmacological Raw Materialsmentioning
confidence: 99%